Mechanical Circulatory Support for Right Ventricular Failure - Ersilia M DeFilippis; Veli K Topkara; Ajay J Kirtane; Koji Takeda; Yoshifumi Naka; A Reshad Garan (Cardiac Failure Review)
Right ventricular (RV) failure is associated with significant morbidity and mortality, with in-hospital mortality rates estimated as high as 70–75%. RV failure may occur following cardiac surgery in conjunction with left ventricular failure, or may be isolated in certain circumstances, such as inferior MI with RV infarction, pulmonary embolism or following left ventricular assist device placement. Medical management includes volume optimisation and inotropic and vasopressor support, and a subset of patients may benefit from mechanical circulatory support for persistent RV failure. Increasingly, percutaneous and surgical mechanical support devices are being used for RV failure. Devices for isolated RV support include percutaneous options, such as micro-axial flow pumps and extracorporeal centrifugal flow RV assist devices, surgically implanted RV assist devices and veno-arterial extracorporeal membrane oxygenation. In this review, the authors discuss the indications, candidate selection, strategies and outcomes of mechanical circulatory support for RV failure.